The Basic Role of Islamic Education Management in Human Resource Management in the Digital Era - Suci Hartati (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
In the digital era, Islamic educational management plays a fundamental role in developing human resources (HR) who are not only technologically competent but also uphold Islamic values. The digital transformation in education requires HR management that can integrate Islamic principles with digital skills suited to today’s educators. This study aims to analyze the fundamental role of Islamic educational management in planning, organizing, implementing, and supervising HR management in the digital era, as well as to identify relevant strategies for achieving a balance between technology and Islamic values. The methodology used is a qualitative approach through a literature review that includes examining Islamic educational management theories and analyzing the application of modern management approaches, such as the hierarchy of needs, contingency theory, and transformational leadership. The results indicate that integrating management functions with Islamic principles effectively supports the development of educators who possess both technological competencies and Islamic character. Flexible organization, technology-based training planning, and ethics-based supervision have proven effective in shaping HR that is adaptable to digital changes. The implications of this study suggest that Islamic educational institutions can strengthen HR quality through management strategies that balance technological skill development with character-building. This approach not only enhances educational effectiveness in the digital era but also reinforces the Islamic values embedded in every aspect of HR management.